Pemanfaatan Teknologi Informasi dan Komunikasi Berbasis Aplikasi Media Sosial dalam Mendukung Penerapan Bidang Ilmu Jurnalistik di Era Digital - Norbertus Tri Suswanto Saptadi; Sean Coonery Sumarta (Abdimas Universal, 2023)
The use of Social Media (Medsos) applications and the integration of Information and Communication Technology (ICT) has developed and is influential in various fields of human life. The use of computers in the digital era is part of the life of Catholic Youth. The correct use of computers in various OMK activities can increase effectiveness, efficiency and measurability. The existence of the journalistic field can influence the ability and increase the creative power and sensitivity of OMK in filling public spaces. However, various journalistic activities such as reporting and publication carried out by OMK through various means such as social media are often still constrained by aspects of knowledge, attitudes and skills. This causes various OMK activities to not be able to make a positive and real contribution so that journalistic training is needed. The aim of training for OMK is to enrich knowledge, shape attitudes and improve skills for various ICT-based journalistic activities. Journalistic training methods include the first stage: pre-training (questionnaire), the second stage: training implementation (lectures, writing practice, presentations), and the third stage: training evaluation (interviews and questionnaires). The results of journalism training showed good and very good values ​​in the cognitive aspects of 35 people or 71.42%, affective 42 people or 85.71%, and psychomotor 36 people or 73.46% so it is hoped that OMK can improve various journalistic activities by utilizing ICT in the digital era so that it becomes professional.